A new implementation of the reconfigurable analog baseband low pass filter with cell-based variable transconductance amplifier - Alaybeyoğlu, Ersin; Kuntman, Hakan; Alaybeyoğlu, Ersin (Springer, 2018)
In this study, a new implementation of reconfigurable analog baseband (ABB) low pass filter employing cell-based variable transconductance amplifier (cell-based VTA) is presented for multi-standard transceivers. The configurability of the designed filter is supported by activating different cells and changing biasing currents of each cell. Multi-standard transceivers allow to process different protocols in a single chip. These type transceivers need reconfigurable analog elements. In this work reconfigurable ABB low-pass filter is designed to support the application of Bluetooth, CDMA2000, Wideband CDMA, and IEEE 802.11a/b/g/n wireless LANs and 2G/3G/4G. The designed filter operates between 20 kHz and 40 MHz. The minimum value of the designed filter's third order intersection point is 21.4 dBm. The performance of the designed circuit is tested with TSMC 0.18 mu m technology in CADENCE environment.
10th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 30-DEC 02, 2017 -- Bursa, TURKEY
Keywords: Analog Baseband; Frequency Agile Filter; Cell-Based Variable Gain Amplifier; Cell-Based Variable Transconductance Amplifier; G(M)-C Filter; Operational Transconductance Amplifier